2013
DOI: 10.2147/ott.s43287
|View full text |Cite
|
Sign up to set email alerts
|

Treatment outcome of advanced pancreatic cancer patients who are ineligible for a clinical trial

Abstract: ObjectiveThe aim of this study was to evaluate the outcome of patients with advanced pancreatic cancer in clinical practice, and assess whether chemotherapy provided a clinical benefit for patients who did not meet the eligibility criteria of the clinical trial.MethodsWe retrospectively analyzed the medical records of 75 patients who received first-line chemotherapy for pancreatic cancer between April 2006 and September 2011. Patients were treated with gemcitabine (GEM) alone, S-1 (tegafur, gimeracil, and oter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
1

Year Published

2015
2015
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(8 citation statements)
references
References 16 publications
(11 reference statements)
1
6
1
Order By: Relevance
“…These findings are consistent with the results of a previous study indicating that > 55% of melanoma patients were ineligible for an immunotherapy trial . Moreover, similar results were observed in studies examining eligibility for phase III trials of new drugs other than ICBs in other malignancies, such as lung, renal, breast, and pancreatic cancers . The ineligibility rate observed in our study was significantly higher than that of 4.2% (0–10.6%) reported in a study in a similar setting in Japan before 2000 .…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…These findings are consistent with the results of a previous study indicating that > 55% of melanoma patients were ineligible for an immunotherapy trial . Moreover, similar results were observed in studies examining eligibility for phase III trials of new drugs other than ICBs in other malignancies, such as lung, renal, breast, and pancreatic cancers . The ineligibility rate observed in our study was significantly higher than that of 4.2% (0–10.6%) reported in a study in a similar setting in Japan before 2000 .…”
Section: Discussionsupporting
confidence: 92%
“…8 Moreover, similar results were observed in studies examining eligibility for phase III trials of new drugs other than ICBs in other malignancies, such as lung, [9][10][11] renal, 12,13 breast, 14 and pancreatic cancers. 15 The ineligibility rate observed in our study was significantly higher than that of 4.2% (0-10.6%) reported in a study in a similar setting in Japan before 2000. 16 However, that study was based on trials and eligibility criteria different from our study.…”
Section: Discussioncontrasting
confidence: 72%
“…Among the 78 articles that were selected on the basis of the inclusion/exclusion criteria, 72 articles were editorials or incomplete data and therefore excluded. Our final sample from 4 randomized clinical trials (level of evidence: 2b) 20 23 and 2 retrospective study (level of evidence: 3b) 24 , 25 that included 1025 patients were collected.…”
Section: Resultsmentioning
confidence: 99%
“…We collected data from 6 studies including a total of 1025 patients. All studies were conducted in Asian countries, including 5 in Japan, 20 22 , 24 , 25 and one Japanese–Chinese collaboration article. 23 The patient-level analyses showed that patient age varied from 40 to 70.…”
Section: Resultsmentioning
confidence: 99%
“…In the clinically ineligible arm, median PFS was 1.1 months, and median OS was 2.9 months. The outcomes for patients who did not meet the eligibility criteria were poor [ 95 ]. Hence, it is important to determine which patients could benefit from chemotherapy vs. optimal supportive care.…”
Section: Molecularly Targeted Treatment Strategiesmentioning
confidence: 99%